Strategy Pemanfaatan Instagram Sebagai Media Komunikasi Dan Penjualan Fashion Muslim Online (Studi Deskriptif Kualitatif Akun Instagram @zilohijab) - Gan Gan Giantika (Jurnal Komunikasi, 2019)
The digital age makes communication enter a new phase. The widespread use of gadgets nowadays, making activities through gadgets more often done. New technology is increasingly advanced, the internet is increasingly easy to access, more applications and social media to communicateare also increasingly diverse. One service product that was born thanks to internet acces is social network, namely Instagram. Instagram is a social media that has visual power. With this power, many individuals and companies use it to attract the attention of the public, one of them is the @zilohijab Instagram account. This study wants to reveal the use of Instagram as a means of communication an sales of Muslim fashion on the Instagram account @zilohijab. The method used by researchers in this study is a descriptive qualitative research method. In the discussion of this study resulted in several strategies used by @zilohijab in planning the content of messages on his Instagram account including Instagram @zilohijab with the concept of Trusted Muslim Fashions used as a teaser, approaching through community building, working with influencers to produce content and product curation, as well as designing story to strengthen visual content with an emotionless strategy. The conclusion in this study is that the strategy designed by @zilohijab has been carried out to the maximum because the strategy is based on the concept and character. Keywords : Strategy, Instagram, Media Communications, Sales